Investigating the Relationship Between Linguistic Variables and Executive Functions in Persian-speaking Children Aged 5-8 Years With and Without Developmental Language Disorder - Hoda Mowzoon; Fatemeh Hassanati; Reza Nilipour; Mohammad Reza Mohammadzamani; Zahra Sadat Ghoreishi (Journal of Rehabilitation)
Objective Developmental language disorder is a type of language disorder that starts in childhood and can involve all language levels. This disorder is not specific to language; other skills, such as cognitive skills, are also damaged in these children. Executive functions are one of the highest cognitive levels studied in these children in recent years. This study investigates the performance of two parts of executive functions, including selective attention and problem-solving/organization, and their relationship with language variables in these children. Materials & Methods This was a descriptive-analytical and cross-sectional comparative study. The participants of this research included 56 normal children and 20 children with developmental language disorders in the age range of 5 to 8 years. All the subjects were examined using the tower of London test, stroop task (the moon and the sun) to assess executive functions and verbal fluency test, and Persian language development battery to assess language functions. All analysis was done using the SPSS software, version 18. Results According to the findings of this research, both groups of participants showed significant differences in the linguistic variables of syntactic complexity and syntactic comprehension (P<0.05); however, no significant difference was seen in other language variables, including verbal fluency, type-token ratio, number of utterances, and repetition. In executive function skills, an important difference was observed in the number of errors made during the tower of London test (P<0.05). However, in other components of this test, including total score, total time, delay time, and task completion time, as well as selective attention skills, there was no difference between the two groups. On the other hand, there was a correlation between selective attention and verbal fluency, as well as between problem-solving/organization skills and the linguistic variables of type-token ratio, number of utterances, syntactic comprehension and verbal fluency (P<0.05). Conclusion Children with developmental language disorder performed weaker than their normal peers at different language levels as well as in some executive function skills. There is a causal relationship between some language deficits and executive function deficits. More research is needed to confirm or reject this hypothesis.